Anesthesiologist working area in the operating theater: recommendations to avoid infection - Jaras, Mantas; Didvalė, Daiva; Macas, Andrius (Slauga. Mokslas ir praktika, 2020)
The American Society for Epidemiology of Health Care (SHEA) together with the American Society of Anesthesiologists (ASA), Anesthesia Patient Safety Foundation (APSF) and American Association of Nurse Anesthetists (AANA) have published infection prevention recommendation in the operating room (OR) anaesthesia work zone. It is important to improve hand hygiene (HH) to optimize control of the gloves wearing technique during airway management was comment. Moreover, basic OR environmental disinfection requirements have been identified as laryngoscopes, anaesthesia machines, cart disinfection between cases, sterility during central vein catheterization and etc. Finally, to improve infection prevention practise it is recommended to identify clear plans for the future and give practitioners the opportunity to use the standards. infection in the OR: minimum requirements for HH and localization of antiseptic dispensers were recommended. Also, gloves wearing technique during airway management was comment. Moreover, basic OR environmental disinfection requirements have been identified as laryngoscopes, anaesthesia machines, cart disinfection between cases, sterility during central vein catheterization and etc. Finally, to improve infection prevention practise it is recommended to identify clear plans for the future and give practitioners the opportunity to use the standards.